Social Responsibilities of the Businessman - Bowen, Howard R; Gond, Jean-Pascal; Bowen, Peter Geoffrey (University of Iowa Faculty connections, 2013)
Corporate social responsibility (CSR) expresses a fundamental morality in the way a company behaves toward society. It follows ethical behavior toward stakeholders and recognizes the spirit of the legal and regulatory environment. The idea of CSR gained momentum in the late 1950s and 1960s with the expansion of large conglomerate corporations and became a popular subject in the 1980s with R. Edward Freeman'sStrategic Management: A Stakeholder Approachand the many key works of Archie B. Carroll, Peter F. Drucker, and others. In the wake of the financial crisis of 2008-2010, CSR has again become a focus for evaluating corporate behavior. First published in 1953, Howard R. Bowen'sSocial Responsibilities of the Businessmanwas the first comprehensive discussion of business ethics and social responsibility. It created a foundation by which business executives and academics could consider the subjects as part of strategic planning and managerial decision-making. Though written in another era, it is regularly and increasingly cited because of its relevance to the current ethical issues of business operations in the United States. Many experts believe it to be the seminal book on corporate social responsibility.This new edition of the book includes an introduction by Jean-Pascal Gond, Professor of Corporate Social Responsibility at Cass Business School, City University of London, and a foreword by Peter Geoffrey Bowen, Daniels College of Business, University of Denver, who is Howard R. Bowen's eldest son.